EVALUASI SIFAT KIMIA DAN FISIK GAMBUT DARI BEBERAPA LOKASI DI BLOK C EKS-PLG KALIMANTAN TENGAH - Setiadi I. C.; Yulianti N.; Adji F. F. (Fakultas Pertanian Universitas Palangka Raya, 2016)
This research aims to evaluate of the chemical and physical characteristics from several locations in Block C Ex-MRP, Central Kalimantan. Sampling was using the simple random sampling method with 3 (three) replications point. Laboratory analyzes were carried out at the Department of Agronomy Laboratory and the Analytical Laboratory, University of Palangka Raya. These data were analyzed using the Term of Reference of Land Research Center (1983) as well as the regression and the correlation analysis. The results showed that the character of chemistry and fertility of peat from four locations in Block C Ex-Mega Rice Project in Central Kalimantan have similarities, except P-available and saturation base in Kanamit Barat (tidal peat) is 2 times higher than in Kalampangan and 3 times higher than in Bukit Tunggal (inland peat). Peatsamples of all research locations have advanced level of decomposition (sapric) with a range of fiber content 10,40-32,59%, bulk density 0.17 to 0.26 g cm-3, thewater content 148,88-368,95% and reddish black color. The relationship patterns showed there is two patterns of interconnectedness namely positive relationship and negative among the chemical properties, physical properties as well as between them. It describes the interaction of peat characteristics, which is needs to be considered for the use and management of peatlands in Block C Ex-MRP Central Kalimantan